Extreme weather exposure and support for climate change adaptation. (September 2017) - Ray, Aaron; Hughes, Llewelyn; Konisky, David M.; Kaylor, Charles
Highlights: Individuals experiencing extreme weather activity more likely to support climate adaptation policy. Effect of extreme weather activity on opinion is modest and not consistent across specific adaptation policies. Effect of extreme weather activity on opinion diminishes over time. Abstract: Policy efforts to address climate change are increasingly focused on adaptation, understood as adjustments in human systems to moderate the harm, or exploit beneficial opportunities, related to actual or expected climate impacts. We examine individual-level determinants of support for climate adaptation policies, focusing on whether individuals' exposure to extreme weather events is associated with their support for climate adaptation policies. Using novel public opinion data on support for a range of adaptation policies, coupled with high resolution geographic data on extreme weather events, we find that individuals experiencing recent extreme weather activity are more likely to support climate change adaptation policy in general, but that the relationship is modest, inconsistent across specific adaptation policies, and diminishes with time. The data thus suggest that experiencing more severe weather may not appreciably increase support for climate adaptation policies.